Let's fight inequality

Algebra Level 4

{ 6 x 2 1 + 9 x 2 = y 6 y 2 1 + 9 y 2 = z 6 z 2 1 + 9 z 2 = x \begin{cases} \dfrac{6x^{2}}{1+9x^{2}}=y \\ \dfrac{6y^{2}}{1+9y^{2}}=z \\ \dfrac{6z^{2}}{1+9z^{2}}=x \end{cases}

Find the sum of x + y + z x+y+z of all the ordered real triplets ( x , y , z ) (x, y, z) satisfying the system of equations above.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jul 21, 2017

A trivial solution to the system of equations is x = y = z = 0 x=y=z=0 or ( x , y , z ) = ( 0 , 0 , 0 ) (x,y,z)=(0,0,0) . For x , y , z 0 x, y, z \ne 0 , we can consider the reciprocal of each of equation as follows.

{ 6 x 2 1 + 9 x 2 = y 1 6 x 2 + 3 2 = 1 y . . . ( 1 ) 6 y 2 1 + 9 y 2 = z 1 6 y 2 + 3 2 = 1 z . . . ( 2 ) 6 z 2 1 + 9 z 2 = x 1 6 z 2 + 3 2 = 1 x . . . ( 3 ) \begin{cases} \dfrac{6x^{2}}{1+9x^{2}}=y & \implies \dfrac 1{6x^2} + \dfrac 32 = \dfrac 1y & ...(1) \\ \dfrac{6y^{2}}{1+9y^{2}}=z & \implies \dfrac 1{6y^2} + \dfrac 32 = \dfrac 1z & ...(2) \\ \dfrac{6z^{2}}{1+9z^{2}}=x & \implies \dfrac 1{6z^2} + \dfrac 32 = \dfrac 1x & ...(3) \end{cases}

( 1 ) + ( 2 ) + ( 3 ) (1)+(2)+(3) and rearrange:

1 6 x 2 1 x + 3 2 + 1 6 y 2 1 y + 3 2 + 1 6 z 2 1 z + 3 2 = 0 1 x 2 6 x + 9 + 1 y 2 6 y + 9 + 1 z 2 6 z + 9 = 0 ( 1 x 3 ) 2 + ( 1 y 3 ) 2 + ( 1 z 3 ) 2 = 0 \begin{aligned} \frac 1{6x^2} - \frac 1x + \frac 32 + \frac 1{6y^2} - \frac 1y + \frac 32 + \frac 1{6z^2} - \frac 1z + \frac 32 & = 0 \\ \frac 1{x^2} - \frac 6x + 9 + \frac 1{y^2} - \frac 6y + 9 + \frac 1{z^2} - \frac 6z + 9 & = 0 \\ \left(\frac 1x - 3\right)^2 + \left(\frac 1y - 3\right)^2 + \left(\frac 1z - 3\right)^2 & = 0 \end{aligned}

Since ( 1 x 3 ) 2 0 \left(\dfrac 1x - 3\right)^2 \ge 0 , ( 1 y 3 ) 2 0 \left(\frac 1y - 3\right)^2 \ge 0 and ( 1 z 3 ) 2 0 \left(\frac 1z - 3\right)^2 \ge 0 , for the L H S = R H S = 0 LHS=RHS=0 , all the three square factors are simultaneously equal to 0. That is x = y = z = 1 3 x=y=z = \frac 13 or ( x , y , z ) = ( 1 3 , 1 3 , 1 3 ) (x,y,z)=\left(\frac 13,\frac 13,\frac 13 \right) .

Therefore, the sum of all x + y + z x+y+z is 0 + 0 + 0 + 1 3 + 1 3 + 1 3 = 1 0+0+0+\frac 13 + \frac 13 + \frac 13 = \boxed{1} .

Rui-Xian Siew
Jul 20, 2017

It's obvious that x , y , z x, y, z are non-negative numbers smaller than 1. Furthermore, since ( 3 x 1 ) 2 0 (3x-1)^{2}\geq 0 , we have

9 x 2 + 1 6 x 9x^{2}+1\geq 6x

1 6 x 9 x 2 + 1 1\geq \frac{6x}{9x^{2}+1}

x 6 x 2 9 x 2 + 1 x\geq \frac{6x^{2}}{9x^{2}+1}

Thus, x y z x x\geq y\geq z\geq x

x = y = z \Rightarrow x=y=z

x = y = z = 1 3 \Rightarrow x=y=z=\frac{1}{3} , or x = y = z = 0 x=y=z=0

Therefore the answer is 0 + 3 ( 1 3 ) = 1 0+3(\frac{1}{3})=1

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...